Implications Of Legal Protection Of Intellectual Property Rights For Obtaining Economic Benefits - Sanusi Sanusi; Ervin Hengki Prasetyo; Moh Taufik (International Journal of Law and Society, 2024)
Intellectual property rights are an implication of the development of international trade, especially in industrial countries. In developing countries, the understanding and protection of intellectual property rights receives less attention, which causes many violations of intellectual property rights and harms creators and inventors. Intellectual property rights have an important role in economic traffic, both regional and international, including investment in a country to spur economic growth of the country and its people. Indonesian society, which is diverse in culture, religion and ethnicity, has very rich creative works, and must take part in the utilization of intellectual property rights. Legal protection and use of copyright are very necessary to become a source of development for the national economy and Indonesian society This research is aimed at examining the implications of Intellectual Property Rights on economic benefit gains. An owner of Intellectual Property Rights as a creative subject must obtain a guarantee of legal protection on his or her work. The result shows that the form of legal protection of intellectual property rights is that the owner of intellectual property rights in performing his or her rights must be protected by law. The economic rights owned by the owner will gain economic benefits if it is performed. The rights include the rights to use, to produce, to publish, to copy, to import, to export and to grant a license (permit) to another party that is intended to make use of the intellectual property. In a condition of law violation, the Law of Intellectual Property Rights as a preventive effort will give a right to an owner of intellectual property rights to sue on civil, criminal, or administrative law. The sanctions on the law breaker are also already written in each law of intellectual property rights that includes copy right, brand right, patent right, graphic design right, and integrated circuit lay-out right. The reason why an owner does not automatically gain economic benefits from his or her work is because he or she does not use the economic rights that he or she has. Some matters causing it are quite high costs of production, difficult licensing, and hard competition. The law protection and economic benefits are two essentials of intellectual property rights. An owner of intellectual property rights is a creative subject that should have those two matters.